Culture Shock and Coping Strategies in International Mobility Program for Indonesian Students in Universiti Selangor Malaysia - Tarisa Febrina Maharani; Desy Misnawati (Dinasti Publisher, 2024)
Culture and communication have a reciprocal relationship. When someone comes to a new place, they will of course face cultural changes and several challenges. This research aims to find out what coping strategies are in overcoming the problem of culture shock at Universiti Selangor among migrant students from Indonesia. The theory used is culture shock theory by (Abbasian, F., & Sharifi 2013). The method used is qualitative, a research method that leads to detailed case research and describes the conditions that actually occur in the study field. The results of the research show that the factors that influence culture shock among Indonesian students at Universiti Selangor are differences in language, learning systems and culture. The process of self-adjustment is important to overcome culture shock, which is carried out through coping strategies, namely methods for controlling and overcoming situations or problems that are considered obstacles. All informants experienced culture shock, however they were still able to adapt over time.